(untitled) (Movimenta (ISSN 1984-4298), 2022)
Aim: To characterize and evaluate the mother-child bond, home opportunities and motor development of infants exposed and non-exposed to HIV between 4 to 12 months of age. Methods: Cross-sectional study with 48 infants and their mothers, 21 exposed to HIV and 27 non-exposed to HIV. Mothers responded to the Mother-Child Bond Assessment Protocol, the Affordances in the Home Environment questionnaire, motor development was assessed by the Alberta Infant Motor Scale (AIMS). Pearson’s correlation was applied, and significance level p-value <0.05. Results: Correlation between mother-child bond and group is positive (r=0,330; p=0,022). Infants exposed to HIV had a lower mother-child bond (p=0,006). Conclusion: There was a relationship between lower mother-child bond among infants exposed to HIV, but there were no differences in relation to motor development and home opportunities.